Implementasi Pendidikan Moderasi Beragama di Sekolah Menengah Atas - Hasan Albana (Jurnal SMART (Studi Masyarakat, Religi, dan Tradisi), 2023)
Intolerant attitudes and behaviors of students, as well as religious moderation education in schools, which is still carried out sporadically, result in segregation between religious communities. This systematic review aims to explore and formulate religious moderation education from various research results in various schools as a prototype. This study is based on the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) guidelines. A systematic search was performed in the Google Scholar database. Initial search based on the title and keywords of religious moderation education in 2018–2022 found 1.001 publications. The determination of the selection resulted in 13 articles for further analysis in this study. The results of the study indicate that the implementation of religious moderation education in schools can be carried out through extracurriculars, special school programs and activities to instill religious moderation, and classroom learning.